Human, Animal and Plant Health Benefits of Glucosinolates and Strategies for Enhanced Bioactivity: A Systematic Review - Maina, Sylvia; Misinzo, Gerald; Bakari, Gaymary; Kim, Ho-Youn (MDPI, 2020)
Glucosinolates (GSs) are common anionic plant secondary metabolites in the order Brassicales. Together with glucosinolate hydrolysis products (GSHPs), they have recently gained much attention due to their biological activities and mechanisms of action. We review herein the health benefits of GSs/GSHPs, approaches to improve the plant contents, their bioavailability and bioactivity. In this review, only literature published between 2010 and March 2020 was retrieved from various scientific databases. Findings indicate that these compounds (natural, pure, synthetic, and derivatives) play an important role in human/animal health (disease therapy and prevention), plant health (defense chemicals, biofumigants/biocides), and food industries (preservatives). Overall, much interest is focused on in vitro studies as anti-cancer and antimicrobial agents. GS/GSHP levels improvement in plants utilizes mostly biotic/abiotic stresses and short periods of phytohormone application. Their availability and bioactivity are directly proportional to their contents at the source, which is affected by methods of food preparation, processing, and extraction. This review concludes that, to a greater extent, there is a need to explore and improve GS-rich sources, which should be emphasized to obtain natural bioactive compounds/active ingredients that can be included among synthetic and commercial products for use in maintaining and promoting health. Furthermore, the development of advanced research on compounds pharmacokinetics, their molecular mode of action, genetics based on biosynthesis, their uses in promoting the health of living organisms is highlighted.
Keywords: QUINONE REDUCTASE-ACTIVITY; BRASSICA-OLERACEA L.; METHYL JASMONATE TREATMENT; ARMORACIA-RUSTICANA ROOT; ANTIMICROBIAL ACTIVITY; ANTIBACTERIAL ACTIVITY; HYDROLYSIS PRODUCTS; BROCCOLI SPROUTS; POTENT INDUCER; ANTIOXIDANT ACTIVITY